1998
DOI: 10.1002/(sici)1096-9071(199803)54:3<186::aid-jmv8>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA sequences and p53 over-expression in laryngeal squamous cell carcinomas in Northeast China

Abstract: One-hundred-two patients with laryngeal squamous cell carcinomas in Northeast China were examined for human papillomavirus (HPV) DNA by the polymerase chain reaction (PCR) coupled with Southern blot hybridization, and for p53 over-expression by immunohistochemical staining. HPV DNAs were found in 60 cases (58.8%). HPV-16, -18, -6, -11, and -33 DNAs were detected in 30 cases, 22 cases, 25 cases, two cases, and one case, respectively. In addition, coinfection either with HPV-6 and -16 or with HPV-6 and -18 was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The HPV DNA was found in 60 cases (58.8%), being the 22 cases,25 cases, 2 cases and 1 case, respectively. Moreover, co-infection either with HPV-6 and -16 or with HPV-6 and -18 was detected in 20 cases (33.3% of HPV DNA-positive cases) (Ma et al, 1998).…”
Section: Larynx Cancersmentioning
confidence: 52%
“…The HPV DNA was found in 60 cases (58.8%), being the 22 cases,25 cases, 2 cases and 1 case, respectively. Moreover, co-infection either with HPV-6 and -16 or with HPV-6 and -18 was detected in 20 cases (33.3% of HPV DNA-positive cases) (Ma et al, 1998).…”
Section: Larynx Cancersmentioning
confidence: 52%
“…A few studies report altogether on approximately 80 patients. [20][21][22][23][24][25][26][27] The prevalence of HPV detection determined by PCR-based techniques for HPV detection in these studies varies from 7% to 59%. The high discrepancy is probably due to differences in number of the examined cases and the methods used in each study.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between HPV and LSCC has not been well established [65]. The largest studies involving LSCC have indicated that the prevalence of HPV infection ranges from 7.4 to 58.8% [10,17,20,38,44]. In a recent case-control study, very low prevalences of HPV DNA and serum antibodies were observed in cases from central Europe and Latin America [55].…”
Section: Discussionmentioning
confidence: 99%